Women's human rights in the Arab-Islamic world - Ewa K. Strzelecka (Oñati Socio-Legal Series)
This article critically examines the tension and possible reconciliation of competing views of culture relativism and the universality of women's human rights in the Arab-Islamic world. A comparative analysis of international human rights instruments, such as the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), and regional human rights protection mechanisms, such as the Cairo Declaration on Human Rights in Islam and the Arab Charter on Human Rights, allow us to get insight into the complexity of the cultural and legal definition and practice of women’s rights within twenty-two States of the Arab Ligue. Particular attention is paid to the national law amendments with regard to transmission of nationality from women to their children and foreign spouses. This is in accordance with the adaptation of the national legislation of the Arab-Islamic countries to the demands of international treaties which guarantee gender equality across the world.